2019
DOI: 10.3389/fphys.2019.00291
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Combination of Whole-Body Neuromuscular Electrical Stimulation and Voluntary Exercise on Metabolic Responses in Human

Abstract: Purpose Since neuromuscular electrical stimulation (NMES) can recruit high-threshold motor units and enhance glucose metabolism, the combination of NMES and voluntary low-intensity exercise would induce both anerobic and aerobic energy consumptions and this type of exercise could be more efficient and effective than conventional exercise regimens. We aimed to investigate metabolic responses and muscle fatigue during whole body NMES (WB-NMES), voluntary exercise, and their combination. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 26 publications
2
27
0
1
Order By: Relevance
“…The blood lactate concentration and RER were significantly increased by superimposing NMES onto the voluntary pedaling exercise at various exercise intensities (middle and lower panels in Figure 2). These findings support the results of previous studies (Watanabe et al, 2014, 2019) and could reflect the recruitment of motor unit/muscle fibers contributing to glucose metabolism. However, at 50% of VT, there was no significant difference in the blood lactate concentration between VOL and VOL+NMES (middle panel in Figure 2), and the increase in the blood lactate concentration during VOL+NMES was significantly lower than the net gain in the blood lactate concentration induced by NMES (lower panel in Figure 3).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The blood lactate concentration and RER were significantly increased by superimposing NMES onto the voluntary pedaling exercise at various exercise intensities (middle and lower panels in Figure 2). These findings support the results of previous studies (Watanabe et al, 2014, 2019) and could reflect the recruitment of motor unit/muscle fibers contributing to glucose metabolism. However, at 50% of VT, there was no significant difference in the blood lactate concentration between VOL and VOL+NMES (middle panel in Figure 2), and the increase in the blood lactate concentration during VOL+NMES was significantly lower than the net gain in the blood lactate concentration induced by NMES (lower panel in Figure 3).…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies, including our work, already reported that the combined application of NMES and voluntary aerobic exercises can increase oxygen consumption and enhance glucose metabolism because of the additional NMES-elicited recruitment of motor units that are not activated for given voluntary exercises and/or high-threshold motor units (Kemmler et al, 2012;Watanabe et al, 2014Watanabe et al, , 2019. On the other hand, the benefit of superimposing NMES onto voluntary exercises would be reduced with high-intensity, anaerobic, or resistance exercises in terms of the additional recruitment of motor units and its induced metabolic responses, since any additional recruitment of motor units by superimposing NMES is theoretically impossible when all motor units are fully recruited, as in the case of maximal voluntary contraction (Hortobagyi et al, 1992;Koutedakis et al, 1995).…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…Several studies have used belt-electrode-type skeletal muscle electrical stimulation with electrodes attached to the torso, thighs, and lower legs to examine its effectiveness on circulatory dynamics, muscle contraction and hypertrophy, and safety in patients with arterial disease and diabetes mellitus [6][7][8][9]. Nowadays, there are novel and useful wearable devices for whole-body neuromuscular electrical stimulation (WB-NMES), rather than the traditional belt type, that efficiently provide electrical stimulation to the forearms and back arms, chest, back, abdomen, oblique abdomen, gluteus muscles, and front and back thigh muscles [10]. Watanabe et al [10] have shown that a combination of aerobic exercise and WB-NMES for 15 min enhances metabolic response to the same extent as high-intensity exercise.…”
mentioning
confidence: 99%